The effect of migration on terror: made at home or imported from abroad? - Dreher, Axel; Gassebner, Martin; Schaudt, Paul (The Canadian journal of economics, 2020)
We analyze how a country's immigrant population—defined as the stock of people born abroad—affects the probability of a terrorist attack in the host country. Using data for 20 OECD host countries and 183 countries of origin over the 1980-2010 period our OLS and 2SLS regressions show that the probability that immigrants from a specific country of origin conduct a terrorist attack in their host country increases with a larger number of foreigners from such countries living there. However, this scale effect does not differ from the effect domestic populations have on domestic terror. We find scarce evidence that terror is systematically imported from countries with large Muslim populations or countries where terror networks prevail. Policies that exclude foreigners already living in a country increase rather than reduce the risk that foreign populations turn violent, and so do terrorist attacks against foreigners in their host country. Highly skilled migrants are associated with a significantly lower risk of terror compared with low skilled ones, while there is no significant difference between foreign-born men and women.
Gesehen am 21.04.2023